Determinants and Status of Vaccination in Bangladesh - Afzal, Nasrin; Zainab, Begum (Dhaka University Journal of Science, 2012)
The identification of the characteristics that have an influence on the vaccination coverage of children and the determination of the pattern of such influence are very important since the government can reschedule the policy to immunize each and every child. This paper examines the factors that manipulate the vaccination coverage in terms of five major vaccines using the Bangladesh Demographic and Health Survey (BDHS)-2007 data. The results strongly suggest that mothers education and economic status play a vital role significantly in improving the vaccination coverage. Besides, Khulna and Rajshahi have higher whereas Sylhet and Chittagong have lower immunization coverage than Dhaka. In addition, mothers exposure to media (newspaper, TV or radio) also improves the status of coverage both in the rural and urban areas in Bangladesh. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10336 Dhaka Univ. J. Sci. 60(1): 47-51 2012 (January)